2021
DOI: 10.1155/2021/6698089
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Periodic Groundwater Table Fluctuation Impact on Chlorinated Vapor Intrusion?

Abstract: Periodic groundwater table fluctuations are found frequently in natural aquifers due to sea tides or seasonal recharge. However, their impact on the transport of volatile organic compounds in the vadose zone released from a groundwater contaminant source (i.e., vapor intrusion) has not been well known. A 2D numerical model was developed to explore vapor intrusion processes in the sandy vadose zone, subject to a fluctuating groundwater table with a range of fluctuation amplitudes and periods. A carcinogenic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Behaviors of nitrogenous compounds and VOCs during GTF. , With the synergistic effects of microorganisms and oxygen content, nitrogenous compounds undergo nitrification and denitrification in unsaturated soil and saturated aquifers. ,,, VOCs migrate into the surface environment by virtue of the capillary fringe and air–water interfaces. …”
Section: Impacts Of Gtf On the Migration Transformation And Retention...mentioning
confidence: 99%
See 3 more Smart Citations
“…Behaviors of nitrogenous compounds and VOCs during GTF. , With the synergistic effects of microorganisms and oxygen content, nitrogenous compounds undergo nitrification and denitrification in unsaturated soil and saturated aquifers. ,,, VOCs migrate into the surface environment by virtue of the capillary fringe and air–water interfaces. …”
Section: Impacts Of Gtf On the Migration Transformation And Retention...mentioning
confidence: 99%
“… The emission of VOCs is dominantly enhanced by the dynamic changes in groundwater diffusion and advection due to GTF. , The emission pathway length of the PCE is determined by the water table depth and amplitude of GTF, and the fluctuations of PCE emissions lag obviously behind GTF due to the damping effects of both the capillary fringe and soil sorption . Additionally, the effect of the capillary fringe was weakened by periodic GTF, a higher concentration of gaseous TCE in fractures appeared in the changing groundwater table compared to that in a stable state, and the concentration of gaseous TCE increased with the amplitude and frequency of fluctuations . A field investigation showed that GTF shortened or lengthened the transport pathway of VOCs and carried dissolved contaminants to unsaturated soil, which enhanced the volatilization potential of VOCs …”
Section: Impacts Of Gtf On the Migration Transformation And Retention...mentioning
confidence: 99%
See 2 more Smart Citations
“…Haberer et al, 22 meanwhile, experimented with a periodically changing boundary and found that, compared with steady-state conditions, highly dynamic variation of the water table enhances the mass transfer of oxygen from the atmosphere into the groundwater. Zhang et al 23 found that the concentration of trichloroethylene at cracks increased 1 order of magnitude compared with that at a static groundwater table when the groundwater table fluctuated by 0.2 m and a duration of 1 day.…”
Section: Introductionmentioning
confidence: 99%